2002
DOI: 10.1021/ja012288d
|View full text |Cite
|
Sign up to set email alerts
|

Locked Nucleic Acid (LNA) Recognition of RNA:  NMR Solution Structures of LNA:RNA Hybrids

Abstract: Locked nucleic acids (LNAs) containing one or more 2'-O,4'-C-methylene-linked bicyclic ribonucleoside monomers possess a number of the prerequisites of an effective antisense oligonucleotide, e.g. unprecedented helical thermostability when hybridized with cognate RNA and DNA. To acquire a detailed understanding of the structural features of LNA giving rise to its remarkable properties, we have conducted structural studies by use of NMR spectroscopy and now report high-resolution structures of two LNA:RNA hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
216
1
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 243 publications
(231 citation statements)
references
References 49 publications
11
216
1
2
Order By: Relevance
“…LNAs are a bicyclic nucleic acid that tether the 2¢-O to the 4¢-C via a methylene bridge (Figure 1), effectively locking the structure into a 3¢-endo sugar conformation. 28,29 This modification provides stabilization against nucleases and also offers the greatest increase in binding affinity of any of nucleic acid modifications in common use today, adding 1.5-6 1C per modification against an RNA target. One study examined the effect that 10 LNA substitutions had on the binding affinity of ASOs upon duplex formation with an RNA target and found that the LNA modifications gave a 24 1C T m increase compared with a DNA control when a PO backbone was used (an average of +2.4 1C per modification) and 16 1C when using a PS backbone (an average of +1.6 1C per modification).…”
Section: Inhibiting Mirna Function With Synthetic Oligonucleotides Dementioning
confidence: 99%
“…LNAs are a bicyclic nucleic acid that tether the 2¢-O to the 4¢-C via a methylene bridge (Figure 1), effectively locking the structure into a 3¢-endo sugar conformation. 28,29 This modification provides stabilization against nucleases and also offers the greatest increase in binding affinity of any of nucleic acid modifications in common use today, adding 1.5-6 1C per modification against an RNA target. One study examined the effect that 10 LNA substitutions had on the binding affinity of ASOs upon duplex formation with an RNA target and found that the LNA modifications gave a 24 1C T m increase compared with a DNA control when a PO backbone was used (an average of +2.4 1C per modification) and 16 1C when using a PS backbone (an average of +1.6 1C per modification).…”
Section: Inhibiting Mirna Function With Synthetic Oligonucleotides Dementioning
confidence: 99%
“…The development of locked nucleic acids (LNAs) will aid the therapeutic applications of miRNAs. In these analogs, the ribose ring is locked by a methylene brigde connecting the 29-O atom with the 49-C atom (Petersen et al 2002). LNAs were shown to exhibit no toxicity at dosages capable of producing antitumor effects in vivo.…”
Section: Therapeutic Implications: Is Pharmacological Modulation Of Mmentioning
confidence: 99%
“…These 2Ј-O,4Ј-Cmethylene-linked bicyclic analogs (Fig. 4A) have the property of locking the deoxyribose ring in the C-3Ј-endo configuration, thereby increasing the local organization of the phosphate backbone (45). LNA modifications were localized within the region of the primer and template predicted to be involved in contacts with the Ty3 RT thumb subdomain (positions Ϫ3 to Ϫ7, defining position Ϫ1 as the first base pair in the catalytic center) (Fig.…”
Section: Ty3 Rt Thumb Mutagenesismentioning
confidence: 99%